Trimethylacetate-bridged mixed-valence binuclear vanadium(IV, V) complexes with a {(VO)2(μ-O)}3+ core. (1st January 2020) - Bazhina, Evgeniya S.; Aleksandrov, Grigory G.; Kiskin, Mikhail A.; Nikitin, Oleg M.; Efimov, Nikolay N.; Ugolkova, Elena A.; Minin, Vadim V.; Magdesieva, Tatiana V.; Sidorov, Aleksey A.; Eremenko, Igor L.
Graphical abstract: The reaction of oxidovanadium(IV) with bpy and pivalate in MeCN gives binuclear V(IV)-V(IV) complex 1 . Similar reactions in EtOH result in mixed-valence V(IV)-V(V) complexes 2 and 3 . In a MeCN solution, the unpaired electron in 2 is delocalized at 293 K and localized on one metal center at 77 K. Abstract: The reaction of an oxidovanadium(IV) salt with an N -donor ligand (2, 2′-bipyridine (bpy) or 4, 4′-di- tert -butyl-2, 2′-bipyridine (dtb-bpy)) and M(piv) (M = Li, K, NBu4 ; piv = (CH3 )3 CCO2 − ) in a ratio of 1:1:2 affords complexes [(VO)2 (µ-OH)(µ-piv)2 (bpy)2 ](otf) (1 ), [(VO)2 (µ-O)(µ-piv)2 (dtb-bpy)2 ](otf)·H2 O (2 ), or [(VO)2 (µ-O)(µ-piv)2 (bpy)2 ](NO3 )·Hpiv·H2 O (3 ), respectively (piv = (CH3 )3 CCO2 −, otf = CF3 SO3 − ). According to single-crystal X-ray diffraction, the complexes contain two vanadium atoms bridged by two carboxylate groups and one hydroxo (1 ) or oxo (2, 3 ) group. Cyclic voltammetry revealed that both vanadium atoms in 1 have oxidation state +4, whereas one of the two metal atoms in 2 and 3 has oxidation state +4 and another one has +5. The room-temperature EPR spectrum of complex 2 in solution is indicative of delocalization of an unpaired electron between two equivalent metal atoms. In frozen glass (77 K) the electron is localized on one center.